2019
DOI: 10.5191/jiaee.2019.26202
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Theoretical and Practical Skills in Agricultural Technical Schools in Haiti: An Exploration of the Curriculum

Abstract: Haiti, with its alarming hunger index, and serious concerns for the population’s food security status, suggests that its agricultural production and productivity are insufficient to guarantee availability of food for the people. Increased productivity supposes the dissemination of best agricultural practices among farmers, and enough qualified extension agents carrying the scientific findings into the rural communities. However, studies in Haiti, have found that the extension activities are mostly conducted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…With many of the opportunities for recent graduates focused on field work, the need for the curriculum to focus on these practical opportunities is evident. Employers mention the lack of field experience inhibits student success which is supported by Calixte et al (2019c) who found the lack of resources made it difficult to implement practical experiences. It is recommended that the schools invest in labs and field equipment to ensure graduates receive practical experience.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…With many of the opportunities for recent graduates focused on field work, the need for the curriculum to focus on these practical opportunities is evident. Employers mention the lack of field experience inhibits student success which is supported by Calixte et al (2019c) who found the lack of resources made it difficult to implement practical experiences. It is recommended that the schools invest in labs and field equipment to ensure graduates receive practical experience.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Based on our theoretical lens, we began the study seeking to understand the phenomena based on the lived experiences of the people most familiar with agricultural TVET in Haiti. This study was conducted in conjunction with additional research on TVET in Haiti (see Calixte et al, 2019a;2019b;and 2019c).…”
Section: Methodsmentioning
confidence: 99%
“…This was deemed appropriate since part of the research team could read and write French and Haitian Creole and part of the team could not. The same process was used in the related research (Calixte et al, 2019a;2019b;and 2019c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation